Indian Armed Forces in 2047: at the centenary of Independence (New Delhi Pentagon, 2023)
The 75th Year of Independence is a milestone in India$1 (Bs march towards a sovereign dispensation characterised by freedom, peace, and prosperity. In that endeavour, the preservation of territorial sanctity, economic sovereignty and political relevance in a competitive intra- and inter-regional dispensation are major challenges. India$1 (Bs geographic situation between two compulsively revisionist, aggressive and militarist neighbours adds to the rigours of such challenges. Wisdom states that as a rising India proceeds to secure her aspirations of peace and prosperity, it would be mandatory to sustain the journey with the possession of robust and military prowess. The purpose of this Vivekananda International Foundation publication is to visualise, candidly, for readers, a futuristic construct of India$1 (Bs military prowess that is sustainable within the nation$1 (Bs affordable defence economics.s
Keywords: Security Sector; Indian Armed Forces; Banerjee, Gautam ed